Analisis Aktivitas Belajar dalam Pembelajaran Sejarah pada Materi Kehidupan Politik dan Ekonomi Bangsa Indonesia pada Masa Demokrasi Terpimpin Kelas XI di SMKN 9 Padang - Madhani, Nisa Fitri; Afriani, Rini (Jurusan Sejarah FIS UNP, 2024)
This research aims to analyze the most dominant types of student learning activities and analyze the factors causing low student learning activities in class XI history learning at SMKN 9 Padang. The informants in this research were 6 class XI students and a class XI history teacher at SMKN 9 Padang. This research uses descriptive methods with qualitative and quantitative approaches. Data collection instruments include questionnaires and semi-structured interviews. The research results show that factors such as student interest, difficulty in understanding the material, a school environment that focuses on the culinary field, and lack of parental support influence student learning activities. It is hoped that this research can improve the quality of teaching, use of technology, create a conducive learning environment, involve parents in learning, and provide adequate facilities as steps to increase student learning activities and achieve history learning goals more effectively.